Rapid low‐temperature synthesis of tetragonal single‐phase Li7La3Zr2O12. Issue 4 (10th January 2017) - Kimura, Teiichi; Yamada, Yusuke; Yamamoto, Kazuo; Matsuda, Tetsushi; Nomura, Hiroshi; Hirayama, Tsukasa
Abstract: The formation of Li7 La3 Zr2 O12 (LLZ), a Li ion conducting oxide with a garnet‐type crystal structure, from a powder mixture of Li2 CO3, La(OH)3, and ZrO2 was investigated, and two possible reaction pathways were identified. Based on the obtained results, LLZ was synthesized at low temperatures and short reaction times, using Li2 CO3, La(OH)3, and La2 Zr2 O7 (instead of ZrO2 ) as starting materials. According to the proposed method, single‐phase LLZ was obtained by heating the initial mixture to 800°C for 1 hour in air, which eliminated possible Li losses. The produced LLZ species exhibited a tetragonal crystal structure with the lattice parameters a= 1.3189(3) nm and c= 1.2694(1) nm, while their transmission electron microscopy images confirmed that LLZ formation occurred through the dissolution of La2 Zr2 O7 and La(OH)3 in a Li2 CO3 melt followed by LLZ precipitation from solution.